THE APPLICATION OF ARTIFICIAL INTELLIGENCE IN LANGUAGE TEACHING (Heritage, 2025)
New technologies are influencing the education system much more than numerous didactic materials because they are blurring the boundaries between formal organized learning environments in schools and the possibilities of informal learning in free time and at home. New technologies challenge students and teachers to adopt a completely new approach to learning and create digital educational spaces. However, due to the complexity of such systems, the development of AI-based foreign language learning environments is adapting to the heterogeneity of students, thus enabling the learning and practice of a language that is still in development. Artificial intelligence platforms could facilitate language teaching by addressing the individual needs and preferences of students, making the learning process more efficient. The integration of artificial intelligence into teaching somewhat improves student outcomes and engagement if it is implemented meaningfully as a supplement, rather than a replacement, for teachers in the educational process. In the process of learning foreign languages, artificial intelligence can be a supplement to teaching materials for the development of reading, writing, listening and speaking skills in foreign languages. Therefore, the aim of this paper is to point out the application of artificial intelligence in language classes, as well as previous scientific research in this area, but also the advantages and disadvantages of artificial intelligence in foreign language teaching.
Keywords: foreign languages, teaching, learning, new technologies, artificial intelligence.